Perancangan Landing Page Sebagai Media Pemasaran Produk Pupuk Organik Cair Biofernic - Slamet, Ahmad Haris Hasanuddin; Hakim, Lukman; Ayyubi, Waridad Umais Al; Pranata, Irzaq Galuh; Ubaidillah, Wildanu (Universitas Negeri Gorontalo, 2025)
Excessive use of chemical fertilizers can reduce soil quality and cause negative environmental impacts. Biofernic is a liquid organic fertilizer made from banana peel and eggshell waste, which is rich in potassium and calcium and beneficial for environmentally friendly plant growth. As a new product, Biofernic requires an effective marketing strategy to be widely recognized, especially by farmers. This study aims to design a website landing page as a digital marketing medium for the Biofernic product. The development method includes needs analysis, system design, coding, testing, and maintenance stages. The landing page was developed using HTML, CSS, and JavaScript with an attractive interface and features such as product information, ordering, and social media integration. The results show that the landing page can serve as an effective tool to introduce the product and expand the market reach of Biofernic.